Legal and ethical analysis of dietary supplement use in the light of anti-doping regulations - Borecki, Marek (Quality in Sport, 2025)
The use of dietary supplements in sports presents both potential benefits and significant regulatory and ethical challenges. This study examines the legal framework governing dietary supplements under international anti-doping policies, particularly the World Anti-Doping Agency (WADA) Code, and analyzes the risks associated with supplement contamination. The research highlights inconsistencies between international and national regulatory approaches, which contribute to varying levels of protection for athletes against unintentional doping violations. Case studies of athletes sanctioned due to contaminated supplements emphasize the urgent need for stricter regulatory oversight and improved athlete education. Ethical concerns regarding fair play, athlete responsibility, and the commercialization of supplements are also discussed. The study concludes that a harmonized regulatory approach, mandatory third-party supplement certification, and enhanced educational initiatives are necessary to reduce the risks associated with dietary supplement use in sports and to uphold the integrity of competition.